Combined treatment of an infected paraurethral cyst - A. A. Kostin; L. V. Shaplygin; N. G. Kulchenkо; A. Mansur (Исследования и практика в медицине)
Paraurethral cysts develop on the site of the paraurethral glands (Skin glands), and are a fairly rare pathology in women. The clinical course of paraurethral cysts is often asymptomatic. However, with an increase in the size of the cyst, women have complaints of frequent urination, dyspareunia, painful sensations in the perineum. Persistent microflora contributes to the aggravation of symptoms, up to the formation of an abscess. With inflammation of the paraurethral cyst, there is still no clear treatment algorithm. In this article, we present an observation of a 29‑year‑old woman with signs of an infected paraurethral cyst. We believe that the administration of antimicrobial drugs to women with signs of skinitis in combination with lower urinary tract infection is necessary for the purpose of preoperative preparation. Surgical treatment of an infected paraurethral cyst consisted of opening the abscess, followed by laser ablation of the inner surface of the cyst capsule. In the postoperative period, the patient also received antimicrobial therapy. We did not detect a recurrence of the paraurethral cyst, observing the patient for 1 year. Conclusion. Combined treatment (a combination of medical and surgical treatment) of an infected paraurethral cyst demonstrates high efficiency.